2004
DOI: 10.1007/s00384-003-0494-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of nuclear factor-?B/RelA is correlated with tumor angiogenesis in human colorectal cancer

Abstract: Our results suggest that increased expression of NF-kappa B/RelA contributes to tumor angiogenesis in colorectal cancer. VEGF may play an important role in mediating the NF-kappa B/RelA angiogenic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 14 publications
2
44
0
Order By: Relevance
“…Once activated, NF-kB promotes cell survival through expression of genes coding for antiapoptotic proteins (c-IAP1, c-IAP2, bfl-1, and Bcl-xl) and supports resistance of tumour cell to treatments by inducing the expression of the multidrug resistance proteins (Pahl, 1999). Furthermore, NF-kB could largely participate to the tumorigenic process through expression of genes coding for growth factors and cell cycle regulators (Van Antwerp et al, 1996;Wang et al, 1996) as well as it could promote metastasis through induction of extracellular matrix-degrading enzymes and angiogenesis through vascular endothelial growth factor expression (Yu et al, 2004). The inhibition of NF-kB could therefore affect tumour cells at different steps of their pathological process.…”
mentioning
confidence: 99%
“…Once activated, NF-kB promotes cell survival through expression of genes coding for antiapoptotic proteins (c-IAP1, c-IAP2, bfl-1, and Bcl-xl) and supports resistance of tumour cell to treatments by inducing the expression of the multidrug resistance proteins (Pahl, 1999). Furthermore, NF-kB could largely participate to the tumorigenic process through expression of genes coding for growth factors and cell cycle regulators (Van Antwerp et al, 1996;Wang et al, 1996) as well as it could promote metastasis through induction of extracellular matrix-degrading enzymes and angiogenesis through vascular endothelial growth factor expression (Yu et al, 2004). The inhibition of NF-kB could therefore affect tumour cells at different steps of their pathological process.…”
mentioning
confidence: 99%
“…The most likely reason that a combination of cytostatic and alpha lipoic acid exerts an inhibitory effect on the NF-κB levels would be strong antioxidant properties of the alpha lipoic acid, which thereby reduce the inducible effect. But the fact that the ALA applied solely and thus was not being able to completely suppress the synthesis and the activation of the NF-κB, acknowledges that cancer cells produce a constitutive NF-κB not only in response to the epigenetic factors (oxidative stress), but most likely as a mode for their survival (25,26,27). This is why it is inexplicable that the combined use of lipoic acid and 5-FU has resulted in increased effect of the cytostatic applied.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the process of angiogenesis plays a central role in local tumor growth and in the development of distant metastases by facilitating the entry of cells into the circulation 1 . Immunohistochemical studies have demonstrated that the intensive formation of tumoral microvessels stimulated by angiogenic factors contributes towards tumor angiogenesis in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%